Molecular mechanisms and consequences of TDP-43 phosphorylation in neurodegeneration - Elise A. Kellett; Adekunle T. Bademosi; Adam K. Walker (Molecular Neurodegeneration)
Abstract Increased phosphorylation of TDP-43 is a pathological hallmark of several neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). However, the regulation and roles of TDP-43 phosphorylation remain incompletely understood. A variety of techniques have been utilized to understand TDP-43 phosphorylation, including kinase/phosphatase manipulation, phosphomimic variants, and genetic, physical, or chemical inducement in a variety of cell cultures and animal models, and via analyses of post-mortem human tissues. These studies have produced conflicting results: suggesting incongruously that TDP-43 phosphorylation may either drive disease progression or serve a neuroprotective role. In this review, we explore the roles of regulators of TDP-43 phosphorylation including the putative TDP-43 kinases c-Abl, CDC7, CK1, CK2, IKKβ, p38α/MAPK14, MEK1, TTBK1, and TTBK2, and TDP-43 phosphatases PP1, PP2A, and PP2B, in disease. Building on recent studies, we also examine the consequences of TDP-43 phosphorylation on TDP-43 pathology, especially related to TDP-43 mislocalisation, liquid–liquid phase separation, aggregation, and neurotoxicity. By comparing conflicting findings from various techniques and models, this review highlights both the discrepancies and unresolved aspects in the understanding of TDP-43 phosphorylation. We propose that the role of TDP-43 phosphorylation is site and context dependent, and includes regulation of liquid–liquid phase separation, subcellular mislocalisation, and degradation. We further suggest that greater consideration of the normal functions of the regulators of TDP-43 phosphorylation that may be perturbed in disease is warranted. This synthesis aims to build towards a comprehensive understanding of the complex role of TDP-43 phosphorylation in the pathogenesis of neurodegeneration. Graphical Abstract TDP-43 is subject to phosphorylation by kinases and dephosphorylation by phosphatases, which variably impacts protein localisation, aggregation, and neurotoxicity in neurodegenerative diseases.